Expression of Recombinant Non Structural 1 Protein of Dengue Virus Serotype-2 in Mammalian Cell Line - FITRIYAH SJATHA; OCTAVIA CHANDRA MUSTIKA; ANGKY BUDIANTI; TJAHJANI MIRAWATI SUDIRO (Indonesian Society for microbiology, 2019)
Dengue infection is a global infectious disease with almost 100 million cases occur annually in over more than 100 endemic countries. Dengue virus (DENV), the causative agent of dengue infection, is an 11 kbp RNApositive strand virus which encode 3 structural and 7 non-structural protein within its genome. Non-structural 1 (NS1) protein of DENV is expressed in the earlier stage of infection and having pathogenic role in disease severity. NS1 gene of DENV serotype-2 Indonesian strain was amplified through PCR method using specific designated primers. NS1 amplicon were then cloned into pUMVC4.a and pcDNA3.1 mammalian expression vector which confirmed through colony PCR and sequencing method. Recombinant pUNS1 and pcNS1 plasmids were transfected into CHO-K1 mammalian cell line with lipid based method. Recombinant NS1 protein expression were analyzed through immunostaining using dengue patient sera and rapid NS1 detection kit. Recombinant pUNS1 and pcNS1 plasmids were successfully constructed and recombinant NS1 protein was expressed in CHOK1 mammalian cell line and shown to be reactive against dengue patient sera. Our recombinant NS1 protein also tend to be released outside the transfected CHO-K1 cells as detected in rapid NS1 detection kit. Recombinant dengue NS1 protein was expressed in mammalian cell line in both intra and extracellularly and shown to be immunogenic.